Loss of Mitochondrial Ca2+ Uniporter Limits Inotropic Reserve and Provides Trigger and Substrate for Arrhythmias in Barth Syndrome Cardiomyopathy. Issue 21 (23rd November 2021) - Bertero, Edoardo; Nickel, Alexander; Kohlhaas, Michael; Hohl, Mathias; Sequeira, Vasco; Brune, Carolin; Schwemmlein, Julia; Abeßer, Marco; Schuh, Kai; Kutschka, Ilona; Carlein, Christopher; Münker, Kai; et al.
Abstract : Background: Barth syndrome (BTHS) is caused by mutations of the gene encoding tafazzin, which catalyzes maturation of mitochondrial cardiolipin and often manifests with systolic dysfunction during early infancy. Beyond the first months of life, BTHS cardiomyopathy typically transitions to a phenotype of diastolic dysfunction with preserved ejection fraction, blunted contractile reserve during exercise, and arrhythmic vulnerability. Previous studies traced BTHS cardiomyopathy to mitochondrial formation of reactive oxygen species (ROS). Because mitochondrial function and ROS formation are regulated by excitation-contraction coupling, integrated analysis of mechano-energetic coupling is required to delineate the pathomechanisms of BTHS cardiomyopathy. Methods: We analyzed cardiac function and structure in a mouse model with global knockdown of tafazzin ( Taz -KD) compared with wild-type littermates. Respiratory chain assembly and function, ROS emission, and Ca 2+ uptake were determined in isolated mitochondria. Excitation-contraction coupling was integrated with mitochondrial redox state, ROS, and Ca 2+ uptake in isolated, unloaded or preloaded cardiac myocytes, and cardiac hemodynamics analyzed in vivo. Results: Taz -KD mice develop heart failure with preserved ejection fraction (>50%) and age-dependent progression of diastolic dysfunction in the absence of fibrosis. Increased myofilament Ca 2+ affinity and slowed cross-bridge cycling caused diastolic dysfunction, in part, compensated by accelerated diastolic Ca 2+ decay through preactivated sarcoplasmic reticulum Ca 2 + -ATPase. Taz deficiency provoked heart-specific loss of mitochondrial Ca 2+ uniporter protein that prevented Ca 2+ -induced activation of the Krebs cycle during β-adrenergic stimulation, oxidizing pyridine nucleotides and triggering arrhythmias in cardiac myocytes. In vivo, Taz -KD mice displayed prolonged QRS duration as a substrate for arrhythmias, and a lack of inotropic response to β-adrenergic stimulation. Cellular arrhythmias and QRS prolongation, but not the defective inotropic reserve, were restored by inhibiting Ca 2+ export through the mitochondrial Na + /Ca 2+ exchanger. All alterations occurred in the absence of excess mitochondrial ROS in vitro or in vivo. Conclusions: Downregulation of mitochondrial Ca 2+ uniporter, increased myofilament Ca 2+ affinity, and preactivated sarcoplasmic reticulum Ca 2+ -ATPase provoke mechano-energetic uncoupling that explains diastolic dysfunction and the lack of inotropic reserve in BTHS cardiomyopathy. Furthermore, defective mitochondrial Ca 2+ uptake provides a trigger and a substrate for ventricular arrhythmias. These insights can guide the ongoing search for a cure of this orphaned disease. Abstract : Supplemental Digital Content is available in the text.